The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15562/bmj.v5i3.295
|View full text |Cite
|
Sign up to set email alerts
|

Chondrogenic Differentiation Capacity of Human Umbilical Cord Mesenchymal Stem Cells with Platelet Rich Fibrin Scaffold in Cartilage Regeneration (In Vitro Study)

Abstract: Background: Human umbilical cord mesenchymal stem cell is a promising source of allogenous MSC with great chondrogenic differentiation capacity. Meanwhile, platelet rich fibrin (PRF) is a natural fibrin matrix, rich in growth factors, forming a smooth and flexible fibrin network, supporting cytokines and cell migration, thus can be used as a scaffold that facilitate the differentiation of MSC. However, the differential capability of MSC cultured in PRF was still poorly understood. Method:We studied in vitro di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
3
4
0
Order By: Relevance
“…PRF administration in osteogenic culture medium unexpectedly stimulates the Aggrecan expression during the early osteogenic differentiation of GMSCs. This result of study is consistent with the research of Sumarta et al [14] which showed that Aggrecan expression increases significantly with PRF administration in culture medium. Furthermore, the triad tissue engineering consists of 3 elements, they are MSCs, natural scaffold and niche.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…PRF administration in osteogenic culture medium unexpectedly stimulates the Aggrecan expression during the early osteogenic differentiation of GMSCs. This result of study is consistent with the research of Sumarta et al [14] which showed that Aggrecan expression increases significantly with PRF administration in culture medium. Furthermore, the triad tissue engineering consists of 3 elements, they are MSCs, natural scaffold and niche.…”
Section: Discussionsupporting
confidence: 93%
“…Growth factor contained in PRF plays an important role to enhance MSCs differentiation capability and acts as advantageous bio-scaffold. Biodegradable polymerized fibrin matrix forms networks that support and stimulate the beneficial MSCs secretome [5,6,14] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the tube is removed from the centrifuge, three layers will appear that are divided into three sections; the lower section consists of red blood cells, the middle section contains PRF and the upper section is formed of acellular plasma. The PRF was then isolated after which the PRF was cut into small pieces using sterile scissors and inserted into each culture plate of the treatment group 22 , 28 , 29 .…”
Section: Methodsmentioning
confidence: 99%
“…About 3-6 ml of blood was extracted with a 10ml syringe before being placed in a plain blood tube and swing centrifuged at 3,000 rpm/min for ten minutes) (Thermofisher, US). The PRF was then placed in a M24 culture plate of the treatment group [7,14].…”
Section: Platelet-rich Fibrin Extractionmentioning
confidence: 99%